2015
DOI: 10.1109/jsac.2015.2432526
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of FSO Communications With Diversity Methods: Add More Relays or More Apertures?

Abstract: This paper targets the performance analysis of Multiple-Input-Multiple-Output (MIMO) point-to-point, singleaperture relay-assisted and MIMO relay-assisted Free-Space Optical (FSO) communications. The objective of the paper is to compare the different FSO diversity methods via an outage probability analysis over gamma-gamma turbulence channels in the case of independent fading among the different apertures of the communicating nodes. Through a well-tailored calculation method, we approximate the gamma-gamma dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…More in detail, we employ the protocols in [29] and [30] for the following two scenarios: i) FSO only: Relay selection for the FSO links without RF links as backups [8], [9] and ii) Independent RF/FSO relay selection: Relay selection and data transmission are performed independently for the RF and FSO links. In the non-BA benchmark schemes, we assume that for the RF links, each time slot is divided into two sub-time slots of equal length for S − R m and R m − D RF transmission.…”
Section: A Benchmark Schemesmentioning
confidence: 99%
“…More in detail, we employ the protocols in [29] and [30] for the following two scenarios: i) FSO only: Relay selection for the FSO links without RF links as backups [8], [9] and ii) Independent RF/FSO relay selection: Relay selection and data transmission are performed independently for the RF and FSO links. In the non-BA benchmark schemes, we assume that for the RF links, each time slot is divided into two sub-time slots of equal length for S − R m and R m − D RF transmission.…”
Section: A Benchmark Schemesmentioning
confidence: 99%
“…The use of different modulation schemes can also alter the system performance as it has been reported that higher modulation schemes like binary phase-shift keying (BPSK) are more immune to channel adversities than the conventional on-off keying (OOK) schemes [19,21]. The diversity in the channel brings in the concept of multiple input multiple output (MIMO), which uses multiple transmitters/receivers to improve the transmission reliability [24,25]. The adoption of diversity schemes not only proved to be a major cost-effective factor in improving the link reliability in FSO systems but also helps improve bandwidth capacity, quality factor (Q), and reduced latency [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Milosevic et al in [12] studied the average BER for a FSO system with a multi-aperture receiver over Málaga (M)-distributed fading channel with pointing errors. The transmission laser selection and repetition coding schemes for a MIMO FSO system were evaluated in [13]. To reduce the impacts of turbulence-induced correlated channel, a polar-coded scheme with and without spatially correlated fading was proposed in [14].…”
Section: Introductionmentioning
confidence: 99%